2020
DOI: 10.1007/s12079-020-00563-6
|View full text |Cite
|
Sign up to set email alerts
|

In silico analyses of the tumor microenvironment highlight tumoral inflammation, a Th2 cytokine shift and a mesenchymal stem cell-like phenotype in advanced in basal cell carcinomas

Abstract: Basal Cell Carcinoma (BCC) represents the most common form of all cancers. BCC is characteristically surrounded by a fibromyxoid stroma. Previous studies have suggested a shift towards a Th2 response, an increase in T regulatory lymphocytes and the presence of cancer-associated fibroblasts in the BCC tumor microenvironment. In this study, we aimed to further characterize the BCC tumor microenvironment in detail by analyzing BCC RNA-Sequencing data and correlating it with clinically-relevant features via in sil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…Th1-mediated interferon-g (IFn-g) is proved to be necessary for facilitating macrophages to kill cancer cells and up-regulating MHC molecules on cancer cells leading to enhance T cell recognition (83,84). On the other hand, the Th2-type cytokine pattern is more preferential in the malignant tumor and participated in cancer progression and immune evasion (85)(86)(87). In addition, Chae's work also revealed that platelets are the source of circulating DKK1 (66).…”
Section: Immunoregulatory Effects Of Dkk1mentioning
confidence: 99%
“…Th1-mediated interferon-g (IFn-g) is proved to be necessary for facilitating macrophages to kill cancer cells and up-regulating MHC molecules on cancer cells leading to enhance T cell recognition (83,84). On the other hand, the Th2-type cytokine pattern is more preferential in the malignant tumor and participated in cancer progression and immune evasion (85)(86)(87). In addition, Chae's work also revealed that platelets are the source of circulating DKK1 (66).…”
Section: Immunoregulatory Effects Of Dkk1mentioning
confidence: 99%
“…Primary RNA-Seq analysis was performed as previously reported ( 44 ). Raw fastq files were curated to remove low-quality reads using FastX-Toolkit.…”
Section: Methodsmentioning
confidence: 99%
“…The expression of CD103 in epithelial skin tumors has hardly been studied. This is surprising since (i) basal cell carcinomas (BCC) [ 91 , 92 , 93 ] and cutaneous squamous cell carcinomas (cSCC) [ 94 , 95 , 96 ] are by far the most common tumors of (especially fair-skinned) humans, (ii) these tumors are usually immunogenic [ 97 , 98 , 99 ], (iii) they often respond to topical and/or systemic immune modulation [ 100 , 101 , 102 , 103 , 104 ], and (iv) their incidence increases greatly upon immunosuppression [ 105 , 106 ]. Moreover, it was already described more than a quarter of a century ago that malignant T cells of cutaneous T cell lymphomas with high CD103 expression migrate preferentially into the E-cadherin-bearing epidermis [ 107 , 108 ].…”
Section: Cd103 In Epithelial Skin Tumorsmentioning
confidence: 99%